Exploring structural equations modelling on the use of modified UTAUT model for evaluating online learning - Stephen Gbenga Fashoto; Yinusa Akintoye Faremi; Elliot Mbunge; Olumide Owolabi (Academy of Cognitive and Natural Sciences, 2024)
The sudden shift from traditional face-to-face classes to online learning during the COVID-19 pandemic has created a need to understand how well online learning is crucial and being accepted, particularly in developing countries. The Internet has enabled international communication and interaction, removing distance and space barriers between Lecturers and students. In some higher education institutions, technology has been gradually integrated into their teaching methods, utilising Learning Management Systems (LMS). This study aims to assess the factors that influence students' intention and use behaviour of online resources using the Unified Theory of Acceptance and Use of Technology (UTAUT). The results show that effort expectancy positively influences students' behavioural intention to use online learning platforms such as Moodle, but facilitating conditions, performance expectancy, and social influence do not. Finally, results in this study also show that students' behavioural intention positively influences students' user behaviour to use the online learning platform. This study suggests that decision-makers should recommend and implement policies to address the challenges students learning from home might face during pandemics to ensure they can continue their education without unnecessary obstacles. This is particularly important in countries like Eswatini, where the cost of internet connectivity is high.